Seropositivity against HPV 16 capsids: a better marker of past sexual behaviour than presence of HPV DNA. Issue 2 (April 1997) - Olsen, A O; Dillner, J; Gjøen, K; Magnus, P
Abstract : OBJECTIVES: To assess if seropositivity to human papillomavirus type 16 capsids is a better marker of sexual history than the presence of HPV DNA. STUDY DESIGN: A population based age stratified random sample of 234 Norwegian women (mean age 32.8 years, range 20-44) was examined for HPV serum antibodies, cervical HPV DNA, cytology and age in relation to sexual behaviour. RESULTS: Neither age nor age at first sexual intercourse was associated with HPV 16 antibodies. Adjusted ORs for 4-5; 6-10 and > 10 versus 0-1 lifetime sexual partners, were 13.1 (95% CI 1.5-110.8), 8.2 (1.0-69.6) and 10.5 (1.2-94.0) for HPV 16 seropositivity, respectively; and 2.6 (0.2-27.8), 3.4 (0.4-31.7) and 4.1 (0.4-42.8) for HPV 16 DNA positivity, respectively. CONCLUSION: Seropositivity to HPV 16 capsids is positively associated with the number of sexual partners, suggesting that HPV 16 is predominantly sexually transmitted. The fact that serology had a stronger association with number of sexual partners than viral DNA suggests that seroreactivity is a better measure of lifetime history of HPV infection.